Metabarcoding the eukaryotic community of a threatened, iconic Mediterranean habitat: Posidonia oceanica seagrass meadows - Turon, Xavier; Zarcero, Jesús; Antich, Adrià; Wangensteen, Owen Simon; Ballesteros, Enric; Cebrian, Emma; Marco-Méndez, Candela; Alcoverro, Teresa (Frontiers in Marine Science, 2023)
Against the accelerating pace of worldwide species extinction, reliable biodiversity assessments are critical, both as baselines and to track potential declines. DNA metabarcoding techniques allow for fast and comprehensive assessment of biodiversity in both terrestrial and marine habitats. However, these methods need to be adapted and standardised for each ecosystem in order to be effective. Seagrass meadows are among the most diverse marine habitats and are irreplaceable in terms of the ecosystem services they provide, yet metabarcoding has never been implemented for these systems. In this study, we developed and tested a protocol for metabarcoding the eukaryotic community of meadows of the iconic species, Posidonia oceanica L. (Delile). This seagrass is the main habitat-forming species in Mediterranean coastal waters and is known for its high diversity due to the structural complexity of its canopy and rhizome structures. This habitat is experiencing a range-wide retreat, and there is an urgent need for fast and efficient methods for its biomonitoring and detection of early changes. Our proposed method involves direct sampling of the community, collecting and processing the leaves and rhizome strata separately. To test the utility of the method in distinguishing between different meadow conditions, we sampled two distinct meadows that differ in their prevailing wind and surge conditions, and a nearby rocky reef for comparison. We then adapted a method and pipeline for COI metabarcoding using generalist primers that target the eukaryote diversity present. We detected a high diversity in the two meadows analysed (3,350 molecular operational taxonomic units, dominated by Metazoa and Archaeplastida) and a clear differentiation of the seagrass samples from those of the nearby rocky reefs. The leaves and rhizomes harboured clearly distinct assemblages, and differences were also detected between the two meadows sampled. This new tool has the potential to deliver big biodiversity data for seagrass habitats in a fast and efficient way, which is crucial for the implementation of protection and management measures for this key coastal habitat.